PENGARUH SISTEM SHOPEE PAY DAN SHOPEE PAY LATER TERHADAP PERILAKU KONSUMTIF MAHASISWA FAKULTAS EKONOMI DAN BISNIS - NUZULA, DELA (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2024)
The Effect of Shopee Pay and Shopee Pay Later Systems on Students' Consumptive Behavior at Universitas Nusantara PGRI Kediri's Faculty of Economics and Business. The basis for this study is that the simplicity of the Shopee e-commerce platform's payment process encourages impulsive and consumptive behavior, which may lead to financial restrictions. This study aims to determine how Shopee Pay and Shopee Pay Later affect students' consumption habits. Proportionate stratified random sampling in cluster techniques is employed in this quantitative study. Using purposeful sampling, 289 students were chosen in total. Multiple linear regression was employed to assess the information gathered using Likert scale questionnaires. The results show that 1) Shopee Pay has a substantial impact on customer behavior, as indicated by its significance value of 0.014 < 0.05; 2) Shopee Pay Later has a beneficial impact on consumer behavior, as indicated by its significance value of 0.000 < 0.05. At a significance level of 0.00, the F-statistic value is 259.134.